Sustainable development, environmentalism, population control and global governance - (:unkn) unknown (My University, 2015)
One aspect of globalization, and one that is far more important than the globalization of consumer goods, is the globalization of ideas. Although many Africans are justifiably critical of the evils of slavery, colonialism and neo-colonialism and their negative impact on traditional African societies, there is remarkably little criticism of ideas from the West. Although some Western ideas are good, many are not. One Western idea that should be scrutinized carefully by Africans is that of “sustainable development”. And sustainable development does not come alone; it is bundled with other ideas that also should be evaluated critically, including environmentalism, population control and global governance.
The 7th annual Ethics Conference
One aspect of globalization, and one that is far more important than the globalization of consumer goods, is the globalization of ideas. Although many Africans are justifiably critical of the evils of slavery, colonialism and neo-colonialism and their negative impact on traditional African societies, there is remarkably little criticism of ideas from the West. Although some Western ideas are good, many are not. One Western idea that should be scrutinized carefully by Africans is that of “sustainable development”. And sustainable development does not come alone; it is bundled with other ideas that also should be evaluated critically, including environmentalism, population control and global governance